Empowerment and beyond: Paradoxes of self-organised work. (1st January 2021) - Sauer, Stefan; Nicklich, Manuel
Abstract : In recent years, empowerment has increasingly become the watchword for work in knowledge-intensive industries. In particular, The Agile Manifesto (2001) and new management approaches such as agile frameworks promise to cut down documentation duties and increase autonomy for knowledge workers. It nonetheless remains an open question whether self-organisation as a structural framework and self-organising as an agentic, team-based process can actually be realised in a holistic manner. By building on insights into the paradox of organising and the paradox of autonomy and control, we consider the conditions under which self-organised work in fact becomes feasible. We therefore focus conceptually on two paradoxes of empowerment and empirically on project teams within software development firms. Our data show that organisations might respond to these paradoxes by structurally and culturally opening up to agile approaches – thereby not only empowering teams, but also enabling them to develop by providing structural and personal resources, qualifications and means for promoting self-awareness.